Exploring consumer awareness of Curculigo Latifolia as a sugar substitute - Mohd Nawi, Nolila; Suboh, Nur Atika (Hh Publisher, 2023)
Lemba or Pinang Puyuh, locally known as Curculigo Latifolia, is a prevalent plant species in Peninsular Malaysia and Borneo Island. Belonging to the flowering plant genus Hypoxidaceae, this plant harbours a sweet protein called Curculin extracted from its fruit. Remarkably, Curculin is 500 times sweeter than sucrose, making C. latifolia a viable low-calorie sweetener for individuals with diabetes or obesity. Despite its potential, many remain unaware of this sweet herb. This paper explores consumer awareness regarding C. latifolia as a sugar substitute. Primary data was gathered through a self-administered survey by employing structured questionnaires. In the Klang Valley, Malaysia, 350 respondents were randomly selected. The collected data were analyzed using descriptive, chi-square, and factor analyses. Surprisingly, 80.9% of respondents had never encountered C. latifolia as a sugar substitute. Chi-square analysis disclosed associations between socio-demographic factors, such as gender, and awareness of C. latifolia. Further investigation via factor analysis identified four influencing factors determining consumer awareness: promotion, health concern, product, and price. Given the potential of natural sugar substitutes like C. latifolia in reducing the risk of diseases like diabetes, effective advertising and promotion are crucial. Increasing consumer awareness and knowledge about this herb will be essential for its future acceptance as a sugar substitute.